Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Natasha Levina, Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to empirically examine the influence of net working capital, firm size, leverage, growth opportunity, and profitability towards cash holding in manufacturing companies listed in Indonesia Stock Exchange from period 2017 – 2019. This study used 36 data from manufacturing companies that have been selected using purposive sampling method. Data processing techniques using multiple regression analysis helped by Eviews version 9.0. The reesult shows that net working capital has positive significant effect on cash holding. While firm size, leverage, growth opportunity, profitability have no significant effect on cash holding. The implication of this study is a proper cash management are needed to determine the optimal amount of cash holding for the company’s needs.